E-Commerce pada Usaha Tas Serut Wabisabi - Elia Brian Baskoro; Jullend Gatc (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Wabisabi drawstring bag business is an entrepreneur in the field of fashion accessories that do not yet have stalls on e-commerce. The ordering and payment process can only be done through social media. In practice, this process takes a long time. In addition, the product management process is not accompanied by categorization in accordance with its category which can make a long product search. This research aims to build a system that has a function as a catalog and can handle transactions online. System development is carried out with the System Development Life Cycle using Rapid Application Development prototyping methods. In addition this study uses the Unified Modeling Language as a modeling of the system. Program development on this website-based application using PHP Framework Laravel 7. The results of this study in the form of a website application for customers and staff. Based on the results of product testing and evaluation stated in accordance with user needs and can be used as a transaction tool.